Ideological and Interpersonal Change in the Radical Protest Movement. (7th August 2014) - Useem, Michael
Abstract : The social organization necessary for a cohesive and effective radical protest movement may create considerable political and social distance between the movement and its recruitment base. However, if attempts at expanding membership do succeed, a large influx of new people has the potential for undermining the radical character of the movement unless processes are present which lead to political socialization and social incorporation. Should these processes be present, substantial transformation in the ideological and interpersonal identities of the newcomers is expected. The American draft resistance movement of the late 1960'S is examined with these issues in mind. Interviews with nearly 100 draft resisters reveal that those lacking prior association with the radical student movement underwent extensive change in their political beliefs and communities of identification, shifting toward a much more radical perspective on American society, increasing their estrangement from pre-resistance milieus, and becoming more involved in protest movement networks. The incorporation processes are briefly discussed.